Experiencias de Violencias Basadas en Género que han Tenido Mujeres Universitarias de la Antonio Nariño al Interior del Claustro (2022)
The objective of this research was to analyze the experiences that women psychology students from the Antonio Nariño University have had within the cloister in the face of gender-based violence, under a qualitative methodological framework of exploratory scope with a phenomenological design and a critical social paradigm. . Thus, a questionnaire created and adapted for this research was applied to 39 women who were studying from the second to the tenth cycle of training within the Faculty of Psychology at any of the Antonio Nariño University locations where this program is offered for the second year. semester of the year 2022-2. In this way, the content analysis technique was implemented for the description and study of the data; whose results were ordered and exposed from the categorization and creation of flows of ideas, word clouds or tables, according to their nature.